Association between nutritional status, food insecurity and frailty amongelderly with low income - Nurzetty Sofia Zainuddin,; Muhammmad Hazrin Husin,; Nur Hidayah Ahmad,; Wong, Yun Hua; Han, Wan Chien; Suzana Shahar,; Munirah Ismail,; Devinder Kaur Ajit Singh, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Aging is associated with increased risk of frailty and malnutrition. However, food insecurity has rarely been highlighted in the elderly population, especially among the low income group. Thus, a cross-sectional study was conducted to determine the association between nutritional status, food insecurity and frailty among elderly in low income residences in Klang Valley. A total of 72 elderly individuals aged 60 years and above was selected (mean age 66 ± 6 years) through convenient sampling. Participants were interviewed to obtain information on socio-demographic, health status, food insecurity and cognitive status. Anthropometrics parameters and frailty assessments was measured using standard criteria. Results showed that 75.0% of the participants had abdominal obesity. Nearly half of the participants were overweight (41.7%), followed by normal (43.0%) and underweight (15.3%). With respect to food insecurity, most of them reported that they had enough food (93.1%). There were significant correlation (p < 0.05) between food insecurity with height (r = -0.263, p = 0.026). Most of the participants were pre-frail (58.3%), frail (27.8%) and followed by non-frail (13.9%). Calcium intake is inversely associated with frailty (t = -2.62, p = 0.011). In conclusion, food insecurity was not a problem, however, half of the subjects were overweight and pre-frail. Three out four subjects had abdominal obesity. There is a need to investigate further the pathogenesis of fat frail in this low income elderly population and formulate effective intervention strategies.